Blackthorn Flower Extract Impact on Glycaemic Homeostasis in Normoglycaemic and Alloxan-Induced Hyperglycaemic C57BL/6 Mice - Irena Crnić; Tajana Frančić; Petar Dragičević; Vedran Balta; Verica Dragović-Uzelac; Domagoj Đikić; Irena Landeka Jurčević (Food Technology and Biotechnology, 2021)
Research background. The use of plants and their extracts in treatments of chronic diseases is widely known in traditional medicine. The aim of this study is to determine the effects of 10-day consumption of blackthorn (Prunus spinosa L.) flower extract on blood glucose, glycaemic load, serum α-amlyase activity and insulin concentration in normoglycaemic and hyperglycaemic (alloxan-induced) mice model. Experimental approach. Normoglycaemic and hyperglycaemic (treated with alloxan, 150 mg per kg body mass) C57BL/6 mice were administered daily, during 10 days, blackthorn flower extract by gavage. The sugar mass concentration within the extract was determined by HPLC analysis. In mice, blood and serum blood glucose concentrations, and oral glucose tolerance test were determined by blood glucometer. Serum insulin concentration was determined by ELISA assay and α-amylase activity by colourimetric assay. Results and conclusions. The blackthorn flower extract increased glucose concentrations in normoglycaemic mice by 30% after the 1st and 5th day and by 17% after the 10th day of consumption. It is a consequence of released sugars because sugar analysis revealed 59.8 mg/L monosaccharides, mainly fructose (55.7 mg/L) and glucose (24.3 mg/L) in the extract. On the contrary, the extract consumption reduced serum blood glucose in hyperglycaemic mice by 29% after 10 days of treatment. Oral glucose tolerance test also confirmed that in the hyperglycaemic group treated with blackthorn flower extract glucose homeostasis was improved and showed decrease in blood glucose. Serum insulin concentration increased by 49% and serum α-amylase activity by 46% after 10 days of treatment with blackthorn flower extract in hyperglycaemic group. Thus, it can be concluded that blackthorn flower extract improved glucose tolerance, enhanced insulin secretion and lowered serum α-amylase activity. Novelty and scientific contribution. The obtained results show for the first time the potential of blackthorn (Prunus spinosa L.) flower extract in hyperglycaemia management.